De Novo Mutation in Non-Tyrosine Kinase Domain of ROS1 as a Potential Predictor of Immune Checkpoint Inhibitors in Melanoma - Ma, Si-Cong; Zhu, Hong-Bo; Wang, Jian; Zhang, Yan-Pei; Guo, Xue-Jun; Long, Li-Li; Guo, Ze-Qin; Wu, De-Hua; Dong, Zhong-Yi; Bai, Xue (Frontiers in Oncology, 2021)
Purpose: Despite the success of targeted therapy in c-ros oncogene 1 (ROS1)-rearranged cancers, especially non-small cell lung cancer (NSCLC), the clinical significance of ROS1 de novo mutation has not yet been understood. We sought to elucidate the predictive effect of ROS1 mutation for immune checkpoint inhibitor (ICI) therapy in melanoma. Methods: The Cancer Genome Atlas (TCGA [n = 10967]) and Memorial Sloan Kettering Cancer Center (MSK [n = 10945]) datasets, as well as two clinical cohorts of melanoma received ICI (CA209-038 [n = 73] and MEL-IPI [n = 110]), were included to explore the prevalence, prognostic effect, and immunotherapeutic predictive effect of ROS1 mutation in melanoma. Overall survival (OS) was defined as the primary outcome. Results: Overall, melanoma accounted for the highest proportion of ROS1 mutation (~ 20%) which made up the majority (~ 95%) of the ROS1-alterated cases. Remarkably, ROS1 mutation yielded longer OS from ICI than the wild-type counterpart in the MSK melanoma population (hazard ratio [HR] 0.47, 95% confidence interval [CI] 0.30-0.74), and two external melanoma cohorts (CA209-038: HR 0.42, 95% CI 0.20-0.89; MEL-IPI: HR 0.55, 95% CI 0.34-0.91), without affecting the prognosis of patients. Elevated tumor mutational burden and enrichment of DNA damage repair was observed in ROS1 mutated patients, providing an explanation for the favorable responses to ICI therapy. Precisely, ROS1 mutation in non-protein tyrosine kinase (PTK) domain but not PTK mutation was responsible for the immunotherapy-specific responses of the ROS1 mutated patients in melanoma. Conclusions: Collectively, ROS1 mutation, specifically the non-PTK mutation, is a potential predictor of ICI therapy in melanoma, which is distinct from the well-established role of ROS1 rearrangement for targeted therapy in NSCLC.